Corrigendum to “keeping people in the loop: socioeconomic valuation of dry forest ecosystem services in the Colombian caribbean region” (Journal of Arid Environments (2021) 188, (104446), (S0140196321000124), (10.1016/j.jaridenv.2021.104446)) (2021)
The authors regret for the miscalculation in the aggregated WTP value. First paragraph in section 3.3 must be as follows: Taking as a reference the mean WTP value (2.02 US$/month), the projection for the whole urban population (8450 urban inhabitants) would rise to 17,069 US$/month. However, we proportionally disregarded the negative responses in the WTP (29%), which resulted in 12,119 USD/month (145,428 US$/year) and 727,114 US$ USD in five years. In this vein, the yearly sum required of IMD-L's inhabitants would be 7514.4 USD/year, only 5% of the WTP's potential economic influx, where 95% of the funds could be diverted to different social and ecological improvements, and PES management and operation. Also, the aggregated value reported in the abstract is: 145,428 US$/year. The authors would like to apologise for any inconvenience caused.